Αναπτυξιακές Προκλήσεις για τους Νέους Ενήλικες: Δεσμοί και Ταυτότητα - Σπαντιδάκη-Κυριαζή, Φωτεινή; Γράψας, Ευστάθιος (Education Sciences, 2017)
The current study examined the relationships among the dimensions of romantic attachment and identity formation. The sample consisted of 237 undergraduate and postgraduate university students from five Greek universities, aged 18-25. The following measures were administered: Close Experiences in Relationships – Revised (ECR-R), Dimensions of Identity Development Scale (DIDS), a demographics questionnaire. Attachment anxiety and avoidance were positively associated with ruminative identity exploration and negatively with the identity commitment dimensions. However, the attachment dimensions were not related with the adaptive dimensions of identity exploration as hypothesized. Gender effect was insignificant.